2021
DOI: 10.18203/2320-1770.ijrcog20213857
|View full text |Cite
|
Sign up to set email alerts
|

Role of ferric carboxymaltose in the treatment of postpartum anemia in a tertiary care hospital in Andhra Pradesh

Abstract: Background: Postpartum iron deficiency anemia is common in India as a consequence of postpartum hemorrhage.  Recent studies have evaluated the use of parenteral iron as a better tolerated treatment modality. Compared with oral iron supplements, parenteral iron is associated with a rapid rise in serum ferritin and hemoglobin and improved maternal fatigue scores in the postpartum period.  Parenteral iron may be considered for the treatment of postpartum anemia. The objective of the study was to evaluate the effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…It has been seen that hematological parameters in patients with moderate-to-severe IDA improve from 6 to 12 weeks after IV iron supplementation and take longer to normalize after oral iron supplementation. 9 , 21–25 Hb may, however, improve significantly within two to four weeks of IV FCM supplementation: an increase of ≥3 g/dL at 2 weeks 26 , 27 to an increase of ≥3 g/dL to 5.49 g/dL at 4 weeks. 20 , 28 Real-world studies have reported a significant increase in Hb levels post FCM administration; 2.6 g/dL at 4 weeks; 21 Hb increase of ≥2 g/dL and ≥3 g/dL were attained by 41% and 20% of subjects, respectively, at 6 weeks; 22 normalized Hb ≤1 year.…”
Section: Discussionmentioning
confidence: 95%
“…It has been seen that hematological parameters in patients with moderate-to-severe IDA improve from 6 to 12 weeks after IV iron supplementation and take longer to normalize after oral iron supplementation. 9 , 21–25 Hb may, however, improve significantly within two to four weeks of IV FCM supplementation: an increase of ≥3 g/dL at 2 weeks 26 , 27 to an increase of ≥3 g/dL to 5.49 g/dL at 4 weeks. 20 , 28 Real-world studies have reported a significant increase in Hb levels post FCM administration; 2.6 g/dL at 4 weeks; 21 Hb increase of ≥2 g/dL and ≥3 g/dL were attained by 41% and 20% of subjects, respectively, at 6 weeks; 22 normalized Hb ≤1 year.…”
Section: Discussionmentioning
confidence: 95%